Bioekologi dan Distribusi Beauveria bassianaserta Identifikasi Hama yang Terinfeksi Secara Alami pada Agroekosistem Kacang Panjang dan Bawang Merah - Dimas Ganda Permana Putra; Zenita Afifah Fitriyani; Mega Darmi Novita (Jurnal Penelitian Pertanian Terapan, 2026)
Dependence on synthetic pesticides for horticultural pest control has caused environmental damage and pest resistance, especially in upstream watershed areas. This study evaluated the effectiveness of the entomopathogenic fungus Beauveria bassiana for controlling major insect pests on long bean (Vigna unguiculata sesquipedalis) and shallot (Allium ascalonicum) and its indirect effects on vegetative growth. Field trials in Mojokerto Regency (June–September 2025) used a randomized block design with one factor: B. bassiana concentration (A0 = control, A1 = 106 spores L-1, A2 = 107 spores L-1, A3 = 108 spores L-1), each with five replications. Primary observations recorded pest incidence and infection by B. bassiana; supporting measurements were plant height and leaf number at 14, 21, 35, and 42 days after planting. Treatments A2 and A3 produced significantly higher pest infection rates identified in Coleoptera, Lepidoptera, and Hemiptera by characteristic white mycelial sporulation compared with the control. Reduced pest pressure in these treatments corresponded with significant increases in plant height and leaf number for both crops. Results indicate that B. bassiana at 107–108 spores L-1 is an effective biocontrol agent against multiple pest orders and can indirectly enhance vegetative vigor, supporting its integration into environmentally friendly IPM programs.